(untitled) (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. de Lima DVT, Ordóñez LL, da Cruz DD. 2021. Plant resource uses and losses in a small maroon community in a Colombian Pacific hot spot. Biodiversitas 22: 3031-3041. The Colombian Pacific is a world biodiversity hotspot, and traditional communities of the region have high cultural diversity, such as the Jovi maroon community, which shows economic and cultural practices rely on regional ecosystem services. This study aimed to conduct an ethnobotanical survey in the Jovi community, specifically focused on the identification of the plants used, the purpose of use, losses in the use of species, the conservation status of the species, and if there are differences regarding plant use knowledge between genres. Participant observation was conducted associated with interviews for data collection with 26 local experts. The Jovi community uses a wide variety of plants (135 species belonging to 57 families). Cultivated species showed the highest use values in the community. The most important uses were medicinal, food, and technological, respectively. Use losses were verified, mainly, for the species used as food. Two species deserve attention, i.e. Minquartia guianensis (Near Threatened - IUCN), and Pelliciera rhizophorae (Vulnerable - IUCN), both obtained by extractivism and have timber use. There was no difference in knowledge between men and women. Cultural changes may be delimiting changes in the use of plant species in the community.